The values of x are 2 and -1.
Solving the equation created by substitution listed in the question:
-2x+14=x²-3x+12
Add 2x to both sides:
-2x+14+2x=x²-3x+12+2x
14=x²-1x+12
Subtract 14 from both sides:
14-14=x²-1x+12-14
0=x²-1x-2
Factoring this, we want factors of -2 that sum to -1; -2(1) = -2 and -2+1=-1:
0=(x-2)(x+1)
Using the zero product property, we know that either x-2=0 or x+1=0:
x-2=0
x-2+2=0+2
x=2
x+1=0
x+1-1=0-1
x=-1
Answer:
d = log 38/log31
d = 1.06
Step-by-step explanation:
31 ^ d = 38
Take log of both sides since the exponential equation have different base (always)
d log 31 = log 38
d = log 38 / log 31
d = 1.58 / 1.491
d = 1.06.
We can actually check to see if this is correct.
Substituting d = 1.06
31^ 1.06 = 38.092
(You see, that's approximately correct)
Keep learning, maths is fun!
Answer:
-5
Step-by-step explanation:
Najsjsiskekasizjnsdkdkdkx